Gambaran Kebiasaan Ibu Hamil Dalam Mengatasi Ketidaknyamanan Selama Kehamilan Di RSUD R. Syamsudin, SH - Vega Ramadhina Putri; Lina Rahmiati; Khalidatunnur Andrianie (Sehat MasadaJurnal, 2018)
Pregnancy is a natural and normal process in reproductive period of women life. Discomfort of pregnancy period is common thing. During 9 months or at the 3 trimesters of pregnancy, pregnant women suffered physical change and also with her psychological to prepare herself for the growth period of the fetus, during labor, and breastfeeding. The such changes can cause interference and obstacles in pregnancy. The purpose of research is to describe the habits of pregnant women how to resolve discomfort condition at R. Syamsudin, SH Hospital in May 2014. This research used descriptive method with cross sectional approach by using 30 respondents as samples. For statistical analysis used is univariate. Results of research are for first trimester are nausea and vomiting (100%); second trimester are difficult defecation, bloating, and heartburn (50%), third trimester is frequent urination (100%). Base on the discomfort condition that happened, commonly practice by pregnant women is waiting for the discomfort goes away by itself. The conclusions of research are the habit that did by pregnant women to resolve discomfort conditions is waiting for the discomfort goes away by itself.